2020
DOI: 10.20448/journal.509.2020.73.306.313
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Education Level and Understanding of Financial Literacy and its Effect on Investment Decisions in Capital Markets

Abstract: This study aims to describe how the educational level of investors influences their understanding of financial literacy and its effect on investment decision making in capital markets. The method used in this research is quantitative descriptive. Data collection was conducted from 7 January to 7 February 2020, by distributing questionnaires to investors who were members of PT Bursa Efek Indonesia. The sample in this study amounted to 108 investors. The research findings show that the level of investor knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
5
15
0
6
Order By: Relevance
“…Meanwhile, while both financial literacy and investing experience had significant positive effects on cryptocurrency ownership, in fact the investment experience had a higher influence on cryptocurrency investment behaviour than financial literacy (Zhao & Zhang, 2021). Moreover, according to Baihaqqy et al (2020), there is a correlation between financial literacy and making financial decisions. Factors of financial literacy can help an investor determine which investments to make and how to analyse investment stages to maximise future earnings.…”
Section: Financial Literacymentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, while both financial literacy and investing experience had significant positive effects on cryptocurrency ownership, in fact the investment experience had a higher influence on cryptocurrency investment behaviour than financial literacy (Zhao & Zhang, 2021). Moreover, according to Baihaqqy et al (2020), there is a correlation between financial literacy and making financial decisions. Factors of financial literacy can help an investor determine which investments to make and how to analyse investment stages to maximise future earnings.…”
Section: Financial Literacymentioning
confidence: 98%
“…Furthermore, based on the specific context demonstrated by the previous study, the suggested conceptual framework could include three new factors: herding, emotional, and financial literacy. According to several researchers, herding (Goyal et al, 2021), emotional (Akinkoye & Bankole, 2020), and financial literacy (Baihaqqy et al, 2020) have significant impact on retail investors' decision making.…”
Section: The Proposed Conceptual Frameworkmentioning
confidence: 99%
“…Asumsi tersebut sejalan dengan penelitian yang dilakukan oleh Mandagie et al (2020) yang mampu membuktikan bahwa pengalaman investasi dan toleransi risiko berpengaruh terhadap keputusan investasi. Hal tersebut sejalan dengan penelitian yang dilakukan oleh (Baihaqqy et al, 2020) dan (Mahastanti, 2011).…”
Section: Pendahuluanunclassified
“…Several previous studies have emphasized the pivotal role of financial literacy in the investment decisionmaking process (Chawla et al, 2022). Baihaqqy et al (2020) argue that a higher level of financial literacy enhances an individual's ability to comprehend the risks and potential returns of investments. Additionally, financial attitudes have been identified as a major factor influencing investment behavior (Jayaraj, 2013).…”
Section: Introductionmentioning
confidence: 99%